Bonding wire

By forming a coating layer with high concentrations of Pd and Ni on the surface of Cu or Cu alloy core material, and adding specific elements and Au, the problem of electrochemical corrosion of Cu bonding wire in high temperature environment is solved, and good bonding reliability and FAB are achieved. shape.

CN119452459APending Publication Date: 2025-02-14NIPPON STEEL CHEM & MATERIAL CO LTD

Patent Information

Application Number
CN202380017072.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-05-30
Filing Date
2023-06-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing Cu bonding wire is prone to electrochemical corrosion in a high temperature environment, resulting in poor bonding reliability of the second joint part, and at the same time, the FAB shape of the bare Cu bonding wire is poor, affecting the bonding properties of the first joint part.

Method used

A core material composed of Cu or Cu alloy is formed on the surface, and a coating layer with a total concentration of Pd and Ni is more than 90 atomic % and a specific element is added to the coating layer, such as Ti, V, Cr, Mn, Fe, Co, Zn, Zr, Nb, Mo, Ru, Rh, Sn, Ta, W, Os, Ir, Pt, Au, Bi, and the surface of the wire contains Au to improve the adhesion and joint reliability of the second joint portion.

Benefits of technology

A good FAB shape and good bonding reliability under high temperature environment are achieved, the adhesion and initial bonding of the second joint are improved, and electrochemical corrosion is suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004940627470000291
    Figure BDA0004940627470000291
  • Figure BDA0004940627470000301
    Figure BDA0004940627470000301
  • Figure HDA0004940627490000011
    Figure HDA0004940627490000011
Patent Text Reader

Abstract

The purpose of the present invention is to provide a novel alloy-coated Cu bonding wire which has a good FAB shape, has good initial bonding properties of a second bonding part, which is represented by adhesion of the second bonding part, and has good bonding reliability of the second bonding part by suppressing electrochemical corrosion in a high-temperature environment. The alloy-coated Cu bonding wire is characterized by comprising a core material comprising Cu or a Cu alloy, and a coating layer formed on the surface of the core material and having a total concentration of Pd and Ni of 90 at% or more, the thickness of the coating layer is 10 nm or more and 130 nm or less in a concentration distribution in the depth direction of a line measured by Auger electron spectroscopy (AES) such that the depth-direction measurement points are 50 or more in the coating layer. When the average value of the ratio CPd / CNi of the Pd concentration CPd (atomic%) to the Ni concentration CNi (atomic%) for all measurement points of the coating layer is defined as X, the average value X is 0.1-35.0, the total number of measurement points in the coating layer having an absolute deviation of 0.3 X or less from the average value X is 50% or more relative to the total number of measurement points of the coating layer, and the following condition (A) is satisfied, where X represents the average value of the ratio CPd / CNi of the Pd concentration CPd (atomic%) to the Ni concentration CNi (atomic%), and X represents the average value of the ratio CPd / CNi of the Pd concentration CPd (atomic%) to the Ni concentration CNi (atomic%). (A) contains one or more elements selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Zn, Zr, Nb, Mo, Ru, Rh, Sn, Ta, W, Os, Ir, Pt, Au, and Bi (hereinafter referred to as a "first additive element"). ) The total concentration of the first additive element with respect to the entire wire is from 5 ppm by mass to 450 ppm by mass (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to bonding wires. Background Art

[0002] The bonding wire is used to connect the electrode formed on the semiconductor chip with the electrode on the lead frame or substrate. The bonding wire connection process uses a cylindrical bonding tool (cutter) through which the bonding wire is passed for connection, and the first bonding is performed with the electrode on the semiconductor chip. Then, after forming a wire arc, the wire portion is secondly bonded to an external terminal such as an electrode on the lead frame or substrate. The first bonding is completed by heating and melting the front end of the wire portion (hereinafter also referred to as the "tail") coming out of the chopper by arc heat input, forming an air-free solder ball (FAB: Free Air Ball; hereinafter also referred to as the "ball") by surface tension, and then the ball portion is crimped and bonded to the electrode on the semiconductor chip (hereinafter also referred to as "ball bonding"). In addition, the second bonding does not form a ball, but is crimped and bonded to the external terminal by applying ultrasonic waves and loads from the chopper to the wire portion (hereinafter also referred to as "wedge bonding").

[0003] Until now, gold (Au) has been the mainstream material for bonding wires, but substitution with copper (Cu) is being promoted, mainly for LSI applications (for example, Patent Documents 1 to 3). In addition, against the background of the popularity of electric vehicles and hybrid vehicles in recent years, in vehicle-mounted equipment applications, and in power equipment (power semiconductor devices) applications in high-power equipment such as air conditioners and solar power generation systems, substitution with Cu, which has high efficiency and reliability, is expected due to its high thermal conductivity and fusing current.

[0004] Cu has the disadvantage of being easily oxidized compared to Au, and as a method of preventing the surface oxidation of Cu bonding wire, a structure in which the surface of a Cu core material is coated with a metal such as Pd has been proposed (Patent Document 4). In addition, a Pd-coated Cu bonding wire has been proposed in which the surface of a Cu core material is coated with Pd and Pd and Pt are added to the Cu core material to improve the bonding reliability of the first bonding portion (Patent Document 5).

[0005] Prior Art Literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 61-48543

[0008] Patent Document 2: Japanese Patent Application No. 2018-503743

[0009] Patent Document 3: International Publication No. 2017 / 221770

[0010] Patent Document 4: Japanese Patent Application Publication No. 2005-167020

[0011] Patent Document 5: International Publication No. 2017 / 013796 Summary of the invention

[0012] Technical problem to be solved by the invention

[0013] In recent years, bonding wires are required to exhibit good bonding reliability even in severe high-temperature environments.

[0014] The present inventors have conducted an evaluation based on such recent demands and found that in the conventional Cu bonding wire with a Pd coating layer, the Pd coating layer is partially peeled off during the wire connection process, and the Cu of the core material is exposed. The contact area between the coated Pd portion and the exposed Cu portion is exposed to an environment containing oxygen, water vapor, and sulfide-based exhaust gas generated from the sealing resin under a high temperature environment, thereby causing local corrosion of Cu, that is, electrochemical corrosion, and sometimes the bonding reliability of the second bonding portion cannot be sufficiently obtained. On the other hand, for the bare Cu bonding wire without a Pd coating layer, although electrochemical corrosion does not occur, the FAB shape is poor, and the bonding of the first bonding portion is insufficient.

[0015] In the process of studying the above-mentioned subject, it was confirmed that the alloy-coated Cu bonding wire in which the surface of the Cu core material is coated with an alloy containing Ni and Pd shows good results in terms of FAB shape and bonding reliability in a high temperature environment due to its alloy coating structure. However, with respect to such alloy-coated Cu bonding wire, it was found that the tightness between the wire terminals at the second bonding portion (hereinafter, also referred to as "the tightness of the second bonding portion") has room for improvement. Hereinafter, in this specification, the tightness of the second bonding portion and the initial bonding strength of the second bonding portion are collectively referred to as the initial bonding of the second bonding portion.

[0016] The present invention provides a novel alloy-coated Cu bonding wire which has a good FAB shape, good initial bonding performance of the second bonding part represented by the adhesion of the second bonding part, and suppresses electrochemical corrosion in a high temperature environment to provide good bonding reliability of the second bonding part.

[0017] Technical means for solving technical problems

[0018] The present inventors have conducted intensive studies on the above-mentioned problems and, as a result, have found that the above-mentioned problems can be solved by having the following configuration, thereby completing the present invention.

[0019] That is, the present invention includes the following contents.

[0020] <1>

[0021] A bonding wire comprising a core material made of Cu or a Cu alloy and a coating layer formed on the surface of the core material and having a total concentration of Pd and Ni of 90 atomic % or more,

[0022] In the concentration distribution in the depth direction of the line measured by Auger electron spectroscopy (AES) so that the number of measurement points in the depth direction is 50 or more in the coating layer,

[0023] The thickness of the coating layer is not less than 10 nm and not more than 130 nm.

[0024] When the Pd concentration C of all measurement points in the coating layer is Pd (atomic %) and Ni concentration C Ni (atomic %) ratio C Pd / C Ni When the average value of is set to X, the average value X is greater than or equal to 0.1 and less than or equal to 35.0,

[0025] The total number of measurement points in the coating layer whose absolute deviation from the average value X is within 0.3X is 50% or more relative to the total number of measurement points in the coating layer.

[0026] The following conditions (A) are met,

[0027] (A) Contains one or more elements selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Zn, Zr, Nb, Mo, Ru, Rh, Sn, Ta, W, Os, Ir, Pt, Au, and Bi (hereinafter referred to as "first additional elements"), and the total concentration of the first additional elements relative to the entire wire is not less than 5 mass ppm and not more than 450 mass ppm.

[0028] <2>

[0029] A bonding wire comprising a core material made of Cu or a Cu alloy and a coating layer formed on the surface of the core material and having a total concentration of Pd and Ni of 90 atomic % or more,

[0030] In the concentration distribution in the depth direction of the line measured by Auger electron spectroscopy (AES) so that the number of measurement points in the depth direction is 50 or more in the coating layer,

[0031] The thickness of the coating layer is not less than 10 nm and not more than 130 nm.

[0032] When the Pd concentration C of all measurement points in the coating layer is Pd (atomic %) and Ni concentration C Ni (atomic %) ratio C Pd / C NiWhen the average value of is set to X, the average value X is greater than or equal to 0.1 and less than or equal to 35.0,

[0033] The total number of measurement points in the coating layer whose absolute deviation from the average value X is within 0.3X is 50% or more relative to the total number of measurement points in the coating layer.

[0034] The following conditions (A) and (B) are met,

[0035] (A) contains one or more elements selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Zn, Zr, Nb, Mo, Ru, Rh, Sn, Ta, W, Os, Ir, Pt, Au, and Bi (hereinafter referred to as "first additional elements"), wherein the total concentration of the first additional elements relative to the entire wire (the concentration of Au is the concentration of the core material) is 5 mass ppm or more and 450 mass ppm or less,

[0036] (B) Au is contained on the surface of the wire, and the concentration of Au is 0.5 mass % or less based on the entire wire.

[0037] <3>

[0038] like <1> or <2> The bonding line is recorded,

[0039] The total number of measurement points in the coating layer whose absolute deviation from the average value X is within 0.2X is 50% or more relative to the total number of measurement points in the coating layer.

[0040] <4>

[0041] like <1> ~ <3> A bonding wire as described in any one of

[0042] For all the measurement points of the coating layer, the least square method was used to calculate the C Pd or C Ni When a straight line approximation is performed, the difference between the maximum value and the minimum value of the approximate straight line within the depth range of the coating layer is 20 atomic % or less.

[0043] <5>

[0044] like <1> ~ <4> A bonding wire as described in any one of

[0045] The concentration distribution in the depth direction of the wire was obtained by digging from the surface of the wire downward in the depth direction by Ar sputtering and measuring by AES under the following conditions:

[0046] Conditions: Positioning is performed so that the center of the wire width is the center of the measurement surface width, the measurement surface width is 5% to 15% of the wire diameter, and the measurement surface length is 5 times the measurement surface width.

[0047] <6>

[0048] like <1> ~ <5> A bonding wire as described in any one of

[0049] One or more elements selected from the group consisting of B, P, and Mg (hereinafter referred to as "second additional elements") are contained, and the total concentration of the second additional elements relative to the entire wire is 1 mass ppm to 100 mass ppm.

[0050] <7>

[0051] like <1> ~ <6> A bonding wire as described in any one of

[0052] It contains one or more elements selected from the group consisting of Se, Te, As and Sb (hereinafter referred to as "third additional elements"), and the total concentration of the third additional elements relative to the entire wire is 1 mass ppm or more and 100 mass ppm or less.

[0053] <8>

[0054] like <1> ~ <7> A bonding wire as described in any one of

[0055] One or more elements selected from the group consisting of Ga and Ge (hereinafter referred to as "fourth additional elements") are contained, and the total concentration of the fourth additional elements relative to the entire wire is 0.011 mass % to 1.5 mass % both inclusive.

[0056] <9>

[0057] like <1> ~ <8> A bonding wire as described in any one of

[0058] One or more elements selected from the group consisting of In and Ag (hereinafter referred to as "fifth additional elements") are contained, and the total concentration of the fifth additional elements relative to the entire wire is 1 mass ppm to 500 mass ppm.

[0059] Effects of the Invention

[0060] According to the present invention, a novel alloy-coated Cu bonding wire can be provided, which has a good FAB shape, good initial bonding performance of the second bonding part represented by the adhesion of the second bonding part, and suppresses electrochemical corrosion in a high temperature environment to provide good bonding reliability of the second bonding part. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 It is a schematic diagram for explaining the second joining portion. Figure 1 It is also a schematic diagram for explaining the position of the evaluation surface (cross section) when evaluating the adhesion of the second bonding portion.

[0062] Figure 2 is Figure 1 A schematic cross-sectional view of the second joining portion when cut along the position indicated by the double-dashed line AA in FIG.

[0063] Figure 3 This is a schematic diagram for explaining the position and size of a measurement surface when performing composition analysis using AES. DETAILED DESCRIPTION

[0064] Hereinafter, the present invention will be described in detail according to preferred embodiments. In the description, reference is sometimes made to the accompanying drawings, but each of the accompanying drawings only schematically shows the shape, size and configuration of the constituent elements to the extent that the invention can be understood. The present invention is not limited to the following embodiments and illustrative objects, and can be implemented with any changes without departing from the scope of protection of the present invention and its equivalent scope.

[0065] [Joining line]

[0066] The bonding wire of the present invention (hereinafter also referred to simply as "the wire of the present invention" or "bonding wire") is characterized in that

[0067] comprising a core material consisting of Cu or a Cu alloy, and

[0068] A coating layer having a total concentration of Pd and Ni of 90 atomic % or more is formed on the surface of the core material.

[0069] In the concentration distribution in the depth direction of the line measured by Auger electron spectroscopy (AES) so that the number of measurement points in the depth direction is 50 or more in the coating layer,

[0070] The thickness of the coating layer is not less than 10 nm and not more than 130 nm.

[0071] When the Pd concentration C of all measurement points in the coating layer is Pd (atomic %) and Ni concentration C Ni (atomic %) ratio C Pd / C Ni When the average value of is set to X, the average value X is greater than or equal to 0.1 and less than or equal to 35.0,

[0072] The total number of measurement points in the coating layer whose absolute deviation from the average value X is within 0.3X is 50% or more relative to the total number of measurement points in the coating layer.

[0073] The following conditions (A) are met,

[0074] (A) Contains one or more elements selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Zn, Zr, Nb, Mo, Ru, Rh, Sn, Ta, W, Os, Ir, Pt, Au, and Bi ("first additional elements"), wherein the total concentration of the first additional elements relative to the entire wire is not less than 5 mass ppm and not more than 450 mass ppm.

[0075] As described above, in recent years, bonding wires are required to exhibit good bonding reliability in harsh high-temperature environments. For example, bonding wires used in vehicle-mounted equipment are required to have bonding reliability in high-temperature environments exceeding 150°C. The inventors of the present invention have conducted an evaluation based on the characteristics required in recent years and found that in the existing Cu bonding wires with a Pd coating, electrochemical corrosion occurs in a high-temperature environment, and sometimes the bonding reliability of the second bonding portion cannot be fully obtained. In addition, for bare Cu bonding wires without a Pd coating, although electrochemical corrosion does not occur, the FAB shape is poor, and the crimping shape of the first bonding portion is poor, which is insufficient for the narrow pitch connection required for high-density mounting.

[0076] In view of this, the inventors have found that a good FAB shape is achieved, and electrochemical corrosion is suppressed in a high temperature environment to achieve good bonding reliability of the second bonding portion, according to the following bonding wire, which includes a core material composed of Cu or a Cu alloy and a coating layer formed on the surface of the core material and having a total concentration of Pd and Ni of 90 atomic % or more, wherein in a concentration distribution in the depth direction of the wire measured by AES in such a manner that the number of measurement points in the depth direction in the coating layer is 50 or more, the thickness of the coating layer is 10 nm or more and 130 nm or less, and when the Pd concentration C of all the measurement points of the coating layer is 90 atomic %, the thickness of the coating layer is 10 nm or more and 130 nm or less, and when the Pd concentration C of all the measurement points of the coating layer is 90 atomic %, the thickness of the coating layer is 10 nm or more and 130 nm or less. Pd (atomic %) and Ni concentration C Ni (atomic %) ratio C Pd / C Ni When the average value of is set to X, the average value X is greater than or equal to 0.1 and less than or equal to 35.0, and the total number of measurement points in the coating layer whose absolute deviation from the average value X is within 0.3X is greater than or equal to 50% of the total number of measurement points in the coating layer.

[0077] On the other hand, regarding such an alloy-coated Cu bonding wire, as described below, it was found that the initial bonding property of the second bonding portion, in particular, the adhesion property of the second bonding portion, has room for improvement.

[0078] As described above, in the second joining, the wire is crimped and joined to the external terminal by applying ultrasonic waves and load to the wire portion from the riving knife. Figure 1 A schematic diagram showing a second bonding portion formed on an external terminal (not shown) when viewed from directly above in a direction perpendicular to the main surface of the external terminal is shown. Figure 1 In the embodiment, a second joint portion 10 is formed at the front end of the wire 1 .

[0079] In the second bonding section, it is expected that the wire and the external terminal are in close contact with each other, but in the second bonding section formed using the alloy-coated Cu bonding wire, it is confirmed that there are some places where the wire and the external terminal are not in close contact with each other to a certain extent, and the close contact between the wire and the terminal is sometimes poor. Figure 1 A schematic cross-sectional view of the second bonding portion when the position indicated by the double-dashed line AA in FIG. 1 is cut in a direction perpendicular to the main surface of the external terminal is shown in FIG. Figure 2 .exist Figure 2 In the embodiment, the second bonding portion 10 is formed on the external terminal 50. However, the inventors have found that the second bonding portion formed using the alloy coated Cu bonding wire has a Figure 2 There is a tendency that there is a portion where the wire and the external terminal are not in close contact over a certain width starting from the left and right ends of the second bonding portion 10 in the bonding wire. Such a problem of the close contact of the second bonding portion is not obvious at least in the conventional bonding wire represented by the bare Cu bonding wire, and therefore it is considered to be a specific issue caused by the use of the above-mentioned specific alloy coating.

[0080] In this regard, the present inventors have found that, according to a bonding wire coated with the above-mentioned specific alloy and satisfying the above-mentioned condition (A), the excellent effect exerted by the use of the specific alloy coating remains unchanged, the close adhesion of the second bonding portion is improved, and good initial bonding properties of the second bonding portion can be achieved.

[0081] <Core Material Made of Cu or Cu Alloy>

[0082] The wire of the present invention includes a core material composed of Cu or a Cu alloy (hereinafter, also simply referred to as a "Cu core material").

[0083] The Cu core material is not particularly limited as long as it is composed of Cu or a Cu alloy, and a known Cu core material constituting a conventional Pd-coated Cu wire known as a bonding wire can be used.

[0084] In the present invention, the concentration of Cu in the Cu core material, for example, in the center (axial portion) of the Cu core material can be set to 97 atomic % or more, 97.5 atomic % or more, 98 atomic % or more, 98.5 atomic % or more, 99 atomic % or more, 99.5 atomic % or more, 99.8 atomic % or more, 99.9 atomic % or more, or 99.95 atomic % or more.

[0085] From the viewpoint of realizing an alloy-coated Cu bonding wire that improves the adhesion of the second bonding portion and provides good initial bonding of the second bonding portion, the Cu core material preferably contains the first additional element so as to satisfy the above condition (A).

[0086] In addition, the Cu core material may contain one or more dopants selected from the second additional element, the third additional element, the fourth additional element, and the fifth additional element described below. The preferred contents of these dopants are described below.

[0087] In one embodiment, the Cu core material is composed of Cu, a first additive element, and inevitable impurities. In other embodiments, the Cu core material is composed of Cu, a first additive element, one or more elements selected from a second additive element, a third additive element, a fourth additive element, and a fifth additive element described later, and inevitable impurities. In addition, the Cu core material may also contain an element constituting a coating layer described later.

[0088] <Coating layer>

[0089] The wire of the present invention includes a coating layer (hereinafter also simply referred to as “coating layer”) formed on the surface of a Cu core material and having a total concentration of Pd and Ni of 90 atomic % or more.

[0090] In order to obtain a good FAB shape and to obtain good bonding reliability of the second bonding portion by suppressing electrochemical corrosion in a high temperature environment, it is important that the coating layer of the wire of the present invention satisfies all of the following conditions (1) to (3) in the concentration distribution in the depth direction of the wire obtained by measuring the concentration points in the depth direction in the coating layer by AES at more than 50 points (hereinafter referred to as "concentration distribution in the depth direction of the wire").

[0091] (1) The thickness of the coating layer is not less than 10 nm and not more than 130 nm,

[0092] (2) The Pd concentration C of all measurement points in the coating layer is Pd (atomic %) and Ni concentration C Ni (atomic %) ratio C Pd / C Ni When the average value of is set to X, the average value X is greater than or equal to 0.1 and less than or equal to 35.0,

[0093] (3) The total number of measurement points in the coating layer whose absolute deviation from the average value X is within 0.3X accounts for 50% or more of the total number of measurement points in the coating layer.

[0094] In the present invention, when AES is used to obtain the concentration distribution in the depth direction of the line, the measurement is performed in a manner that the measurement points in the depth direction become more than 50 points in the coating layer. Generally speaking, the analysis in the depth direction using AES can be analyzed at a sub-nanometer measurement interval, so it is easier to make the measurement points more than 50 points in relation to the thickness of the coating layer that the present invention is the object of. Assume that, when the result of the measurement is that the number of measurement points is less than 50 points, the sputtering speed is reduced or the sputtering time is shortened so that the number of measurement points becomes more than 50 points, and the measurement is performed again. Thus, AES can be used to measure in a manner that the measurement points in the depth direction become more than 50 points in the coating layer, and the concentration distribution in the depth direction of the line is obtained. Although it also depends on the thickness of the coating layer, it is more preferable to determine the measurement point interval of AES in a manner that the total number of measurement points about the coating layer becomes 70 points (more preferably 100 points). Therefore, in a preferred embodiment, the coating layer of the wire of the present invention satisfies all of the above conditions (1) to (3) in the concentration distribution in the depth direction of the wire measured by AES with 50 or more measurement points in the depth direction in the coating layer.

[0095] - Condition (1) -

[0096] Condition (1) relates to the thickness of the coating layer. By including a coating layer satisfying condition (1) in combination with conditions (2) and (3), the wire of the present invention can suppress electrochemical corrosion in a high temperature environment and bring about good bonding reliability of the second bonding portion, and bring about a good FAB shape, thereby bringing about a good crimping shape of the first bonding portion.

[0097] Regarding condition (1), from the perspective of achieving a good FAB shape, the thickness of the coating layer (the calculation method based on the concentration distribution in the depth direction of the line is described later.) is 10nm or more, preferably 12nm or more, 14nm or more, 15nm or more, 16nm or more, 18nm or more, or 20nm or more, more preferably 25nm or more, 30nm or more, 40nm or more, or more than 50nm, and more preferably 60nm or more, 70nm or more, 80nm or more, or more than 90nm. If the thickness of the coating layer is less than 10nm, there is a tendency that eccentricity is generated when the FAB is formed, the FAB shape is deteriorated, and the crimping shape of the first joint is deteriorated. In addition, from the perspective of achieving a good FAB shape, the upper limit of the thickness of the coating layer is 130nm or less, preferably 125nm or less, 120nm or less, 115nm or less, or 110nm or less. If the thickness of the coating layer exceeds 130nm, there is a tendency that irregularity, poor melting, deterioration of the FAB shape, and deterioration of the crimping shape of the first joint are generated when the FAB is formed.

[0098] - Condition (2) -

[0099] Condition (2) relates to the Pd concentration C at all measurement points of the coating layer. Pd (atomic %) and Ni concentration C Ni (atomic %) ratio C Pd / C Ni By including a coating layer that satisfies condition (2) in addition to conditions (1) and (3), the wire of the present invention can suppress electrochemical corrosion in a high temperature environment and bring about good bonding reliability of the second bonding portion, and bring about a good FAB shape, thereby bringing about a good crimping shape of the first bonding portion.

[0100] Regarding condition (2), from the viewpoint of achieving good bonding reliability of the second bonding portion, the average value X is 35.0 or less, preferably 34.0 or less, more preferably 32.0 or less, 30.0 or less, 28.0 or less, 26.0 or less, 25.0 or less, 24.0 or less, 22.0 or less, or 20.0 or less. Pd / C Ni If it exceeds 35.0, there is a tendency that the electrochemical corrosion in the high temperature environment cannot be suppressed and sufficient high temperature bonding reliability cannot be obtained in the second bonding portion. In addition, from the viewpoint of improving the initial bonding strength of the second bonding portion and achieving good initial bonding properties of the second bonding portion, the lower limit of the average value X is 0.1 or more, preferably 0.2 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.8 or more, 1.0 or more, or more than 1.0, more preferably 1.5 or more, 2.0 or more, 2.5 or more, or 3.0 or more. If the average value X is less than 0.1, there is a tendency that sufficient initial bonding properties of the second bonding portion cannot be obtained.

[0101] - Condition (3) -

[0102] Condition (3) involves that the total number of measurement points in the coating layer whose absolute deviation from the above average value X is within 0.3X is greater than 50% relative to the total number of measurement points in the coating layer. By including a coating layer satisfying condition (3) in the combination with conditions (1) and (2), the wire of the present invention can suppress electrochemical corrosion in a high temperature environment and bring about good bonding reliability of the second bonding portion, and bring about a good FAB shape, thereby bringing about a good crimping shape of the first bonding portion.

[0103] Condition (3) together with condition (2) indicates that in the thickness direction of the coating layer, the coating layer contains a PdNi alloy containing Pd and Ni at a predetermined ratio at a high concentration while suppressing the variation of the Pd / Ni ratio. From the viewpoint of achieving a better bonding reliability of the second bonding portion under a high temperature environment and a better FAB shape, it is more preferred that the total number of measurement points in the coating layer whose absolute deviation from the average value X is within 0.2X (more preferably within 0.18X, within 0.16X or within 0.15X) is 50% or more relative to the total number of measurement points in the coating layer.

[0104] From the viewpoint of achieving further good bonding reliability of the second bonding portion under a high temperature environment and from the viewpoint of achieving further good FAB shape, the total number of measurement points in the coating layer whose absolute deviation from the average value X is within a specified range (the preferred range is as described above) is preferably 55% or more or 60% relative to the total number of measurement points in the coating layer, more preferably 65% ​​or more, 70% or more or 75% or more, and further preferably 80% or more.

[0105] From the viewpoint of being able to further enjoy the effect of the present invention, in the concentration distribution in the depth direction of the wire, for all the measurement points in the coating layer, the concentration C of Pd is calculated by the least square method. Pd (atomic %) or Ni concentration C Ni (atomic %), the difference between the maximum and minimum values ​​of the approximate straight line within the depth (thickness) range of the coating layer is preferably 20 atomic % or less, more preferably 15 atomic % or less, further preferably 10 atomic % or less, 8 atomic % or less, 6 atomic % or less, or 5 atomic % or less. In the case where the average value X is less than 1, for all the measurement points of the coating layer, the difference between the maximum and minimum values ​​of the approximate straight line within the depth (thickness) range of the coating layer is preferably 20 atomic % or less, more preferably 15 atomic % or less, further preferably 10 atomic % or less, 8 atomic % or less, 6 atomic % or less, or 5 atomic % or less. Ni When linear approximation is performed for (atomic %), the difference between the maximum value and the minimum value of the approximate straight line within the depth range of the coating layer is preferably within the above range. In addition, when the average value X is greater than 1, for all measurement points of the coating layer, the least square method is used to approximate C Pd When linear approximation is performed for (atomic %), the difference between the maximum value and the minimum value of the approximate straight line within the depth range of the coating layer is preferably within the above range.

[0106] The thickness of the coating layer in condition (1), the average value X in conditions (2) and (3), the absolute deviation from the average value X, the total number of measurement points within a specified range of the absolute deviation, and the ratio of the total number of measurement points within a specified range to the total number of measurement points of the coating layer can be confirmed and determined by digging down from the surface of the wire in the depth direction (toward the center of the wire) by Ar sputtering and performing composition analysis using AES. Specifically, 1) after performing composition analysis on the surface of the wire, by repeating 2) sputtering using Ar and 3) composition analysis on the surface after sputtering, the concentration change of each element in the depth (center) direction (so-called concentration distribution in the depth direction) can be obtained from the surface of the wire, and confirmed and determined based on the concentration distribution. In the present invention, when obtaining the concentration distribution in the depth direction, the unit of depth is SiO 2 Conversion.

[0107] When performing 1) composition analysis of the wire surface and 3) composition analysis of the surface after sputtering, the position and size of the measurement surface are determined as follows. In addition, hereinafter, the width of the measurement surface refers to the size of the measurement surface in the direction perpendicular to the wire axis (the thickness direction of the wire), and the length of the measurement surface refers to the size of the measurement surface in the direction of the wire axis (the length direction of the wire). Figure 3 Further explanation. Figure 3 This is a top view of line 1, with the line axis direction (line length direction) and Figure 3 The vertical direction (up and down direction) corresponds to the vertical direction of the line axis, and the direction perpendicular to the line axis (the thickness direction of the line) corresponds to the vertical direction (up and down direction) of the line axis. Figure 3 The horizontal direction (left and right direction) is represented in a corresponding manner. Figure 3 In the figure, the measurement surface 2 is shown in relation to the line 1, and the width of the measurement surface 2 is the dimension w of the measurement surface in the direction perpendicular to the line axis. a The length of the measuring surface 2 is the dimension l of the measuring surface in the direction of the line axis. a .

[0108] The measurement surface is positioned so that the center of the width of the line in the direction perpendicular to the line axis is the center of the width of the measurement surface, and the measurement surface is determined so that the width of the measurement surface is 5% to 15% of the line diameter. The length of the measurement surface is set to 5 times the width of the measurement surface. Figure 3 In FIG. 1 , the width of the line is indicated by a mark W, and the center of the width of the line is indicated by a dashed line X. Therefore, the measurement surface 2 is positioned so that the center of its width coincides with the dashed line X, which is the center of the width of the line, and the width w of the measurement surface is a The length of the measurement surface is determined so as to be 5% to 15% of the wire diameter (the same value as the wire width W), that is, 0.05W to 0.15W. a Satisfy a =5wa By determining the position and size of the measuring surface as described above, it is possible to accurately determine whether conditions (1) to (3) are met, which are suitable for achieving good bonding reliability of the second bonding portion in a high temperature environment and a good FAB shape. In addition, it is preferred to implement the measurement surface on multiple locations (n≧3) separated from each other by more than 1 mm in the linear axis direction, and use their arithmetic mean.

[0109] The thickness of the coating layer in the above-mentioned condition (1), the average value X in the conditions (2) and (3), the absolute deviation from the average value X, the total number of measurement points where the absolute deviation is within a specified range, and the ratio of the total number of measurement points where the absolute deviation is within a specified range to the total number of measurement points of the coating layer are based on the results measured under the conditions described in the column "Thickness analysis of coating layer using Auger electron spectroscopy (AES)" described later.

[0110] The following describes the tendency of the concentration distribution in the depth direction obtained for the wire of the present invention in one embodiment. From the surface of the wire to a certain depth position, there is a tendency that Pd and Ni coexist at a certain ratio and high concentration, that is, in the region (coating layer) where the total concentration of Pd and Ni is 90 atomic % or more, when the Pd concentration C of all the measurement points of the coating layer is Pd (atomic %) and Ni concentration C Ni (atomic %) ratio C Pd / C Ni When the average value of is set as X, there is a tendency that there are a certain number of measurement points whose absolute deviation from the average value X is within 0.3X. Furthermore, when going in the depth direction, there is a tendency that the concentrations of Pd and Ni decrease and the concentration of Cu increases. In such a concentration distribution in the depth direction, the concentration of Pd C Pd (atomic %) and Ni concentration C Ni (atomic %), the thickness of the coating layer or the total number of measurement points of the coating layer can be obtained from the thickness of the region where the total concentration of Pd and Ni is 90 atomic % or more or the total number of measurement points. Pd / C Ni The average value X can be obtained by performing arithmetic averaging, and the total number of measurement points whose absolute deviation from the average value X is within 0.3X can be obtained by confirming the absolute deviation from the average value X for all measurement points of the coating layer. In addition, as described later, when Au is also contained on the surface of the wire, there is a tendency that the Au concentration decreases and the Pd and Ni concentrations increase from the surface of the wire to the very shallow position in the concentration distribution in the depth direction. In this case, the Pd concentration C is also considered. Pd (atomic %) and Ni concentration C Ni(atomic %), the thickness of the coating layer or the total number of measurement points of the coating layer can be obtained from the thickness of the region with a total of 90 atomic % or more or the total number of measurement points, and the ratio of all measurement points of the coating layer to the total thickness of the coating layer can be calculated. Pd / C Ni The average value X can be obtained by performing arithmetic averaging, and the total number of measurement points having an absolute deviation from the average value X within 0.3X can be obtained by confirming the absolute deviation from the average value X for all measurement points of the coating layer.

[0111] - Other Preferred Conditions of the Coating Layer -

[0112] In the wire of the present invention, in addition to satisfying all of the above conditions (1) to (3), the coating layer preferably further satisfies one or both of the following conditions (4) and (5) depending on the concentration distribution in the depth direction of the wire.

[0113] (4) When the Pd concentration C of all measurement points in the coating layer is Pd The average value of (atomic %) is X Pd When the coating layer is Pd The absolute deviation is 0.1X Pd The total number of measurement points within the coating layer is 50% or more relative to the total number of measurement points of the coating layer.

[0114] (5) The Ni concentration C of all measurement points in the coating layer is Ni The average value of (atomic %) is X Ni When the coating layer is Ni The absolute deviation is 0.1X Ni The total number of measurement points within φ is 50% or more relative to the total number of measurement points of the coating layer.

[0115] In addition, in conditions (4) and (5), the coating layer, its thickness, or the total number of measurement points are as described above in association with conditions (1) to (3). In the case of including a coating layer that satisfies one or both of conditions (4) and (5) in addition to conditions (1) to (3), the wire of the present invention can provide better bonding reliability of the second bonding portion under a high temperature environment and realize a better FAB shape.

[0116] The coating layer may contain, for example, one or more dopants selected from the second additional element, the third additional element, the fourth additional element, and the fifth additional element described below. Preferred contents of these dopants are described below.

[0117] The wire of the present invention may also contain Au on its surface. By containing Au on the surface of the wire, the initial bonding property of the second bonding portion can be further improved. When the wire of the present invention also contains Au on its surface, the concentration of Au relative to the entire wire can generally be set to 0.5 mass% or less, more preferably 0.3 mass% or less or 0.2 mass% or less, and its lower limit can be set to, for example, 0.05 mass% or more, 0.1 mass% or more, etc. Therefore, in one embodiment, the wire of the present invention satisfies the following condition (B),

[0118] (B) Au is contained on the surface of the wire, and the concentration of Au is 0.5 mass % or less based on the entire wire.

[0119] In addition, when the wire of the present invention further contains Au on its surface, when judging whether the above condition (A) is satisfied, the concentration of Au as the first additional element is the following concentration: the concentration of the core material part is determined by exposing the cross section of the wire and measuring the Cu core material part thereof by electron beam microanalyzer (EPMA) or secondary ion mass spectrometry (SIMS). That is, when the wire of the present invention further contains Au on its surface, the "total concentration of the first additional element relative to the entire wire" in the above condition (A) can be understood as "the total concentration of the first additional element relative to the entire wire (wherein the concentration of Au is the concentration of the core material part)" and applied.

[0120] In one embodiment, the wire of the present invention includes a coating layer satisfying the above conditions (1) to (3) and satisfies the following conditions (A) and (B),

[0121] (A) contains one or more elements selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Zn, Zr, Nb, Mo, Ru, Rh, Sn, Ta, W, Os, Ir, Pt, Au, and Bi ("first additional elements"), wherein the total concentration of the first additional elements relative to the entire wire (the concentration of Au is the concentration of the core material) is 5 mass ppm or more and 450 mass ppm or less,

[0122] (B) Au is contained on the surface of the wire, and the concentration of Au is 0.5 mass % or less based on the entire wire.

[0123] According to the alloy-coated Cu bonding wire of the present invention containing the first additional element at the above-mentioned specific concentration, even when the Au concentration on the surface of the wire is low, for example, less than 10 atomic %, less than 8 atomic %, less than 6 atomic %, less than 5 atomic %, less than 4 atomic % or less than 2 atomic %, the adhesion of the second bonding portion can be improved and good initial bonding of the second bonding portion can be achieved.

[0124] The composition analysis of the line surface can be performed under the same conditions as described in 1) the composition analysis of the line surface in connection with the method of obtaining the concentration distribution in the depth direction. That is, when the composition analysis of the line surface is performed using Auger electron spectroscopy (AES), the position and size of the measurement surface are determined as follows.

[0125] The measurement surface is positioned in such a way that the center of the width of the line in the direction perpendicular to the line axis becomes the center of the width of the measurement surface, and the measurement surface is determined in such a way that the width of the measurement surface becomes more than 5% and less than 15% of the line diameter. The length of the measurement surface is set to 5 times the width of the measurement surface. By determining the position and size of the measurement surface as described above, the concentration of Au on the surface of the line suitable for further improving the initial bonding of the second bonding portion can be measured with high precision. In addition, it is preferred to implement the measurement surface at multiple locations (n≧3) separated from each other by more than 1 mm in the line axis direction, and adopt the arithmetic mean thereof.

[0126] The Au concentration on the surface described above is based on the results measured under the conditions described in the column of “Linear surface composition analysis by Auger electron spectroscopy (AES)” described later.

[0127] In the wire of the present invention, the boundary between the Cu core and the coating is determined based on the total concentration of Pd and Ni in the concentration distribution in the depth direction of the wire. The position where the total concentration of Pd and Ni is 90 atomic % is determined as the boundary, the area where the total concentration of Pd and Ni is less than 90 atomic % is the Cu core, and the area where the total concentration of Pd and Ni is more than 90 atomic % is the coating. In the present invention, the boundary between the Cu core and the coating does not necessarily need to be a grain boundary. The concentration distribution is confirmed from the wire surface to the center of the wire, and the thickness of the coating can be calculated as the distance from the depth position Z1 where the total concentration of Pd and Ni first reaches more than 90 atomic % to the depth position Z2 (where Z2>Z1) where the total concentration of Pd and Ni first decreases to less than 90 atomic %.

[0128] The wire of the present invention is characterized in that it includes a coating layer satisfying the above conditions (1) to (3), wherein the average value X, the absolute deviation from the average value X, the total number of measurement points at which the absolute deviation is within a predetermined range, and the ratio of the total number of measurement points at which the absolute deviation is within a predetermined range to the total number of measurement points in the coating layer in accordance with the conditions (2) and (3) are the concentration C of Pd in ​​the coating layer determined by the above boundary determination method. Pd (atomic %) and Ni concentration C Ni (atomic %).

[0129] In one embodiment, the coating layer is composed of Pd and Ni, and inevitable impurities. In other embodiments, the coating layer is composed of Pd and Ni, Au, and one or more elements selected from the first additional element, and inevitable impurities. In another embodiment, the coating layer is composed of Pd and Ni, one or more elements selected from the second additional element, the third additional element, the fourth additional element, and the fifth additional element described later, and inevitable impurities. In another embodiment, the coating layer is composed of Pd and Ni, Au, and one or more elements selected from the first additional element, one or more elements selected from the second additional element, the third additional element, the fourth additional element, and the fifth additional element described later, and inevitable impurities. In addition, the coating layer may also contain elements constituting the above-mentioned Cu core material.

[0130] The thread of the present invention is characterized by satisfying the following condition (A).

[0131] (A) Contains one or more elements selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Zn, Zr, Nb, Mo, Ru, Rh, Sn, Ta, W, Os, Ir, Pt, Au, and Bi ("first additional elements"), wherein the total concentration of the first additional elements relative to the entire wire is not less than 5 mass ppm and not more than 450 mass ppm.

[0132] By including a coating layer that satisfies all of the above conditions (1) to (3) and satisfies the above conditions involving the first additional element, the wire of the present invention can bring about a good FAB shape and good bonding reliability of the second bonding part in a high temperature environment, and improve the tightness of the second bonding part to achieve good initial bonding of the second bonding part.

[0133] Condition (A) relates to the total concentration of one or more elements selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Zn, Zr, Nb, Mo, Ru, Rh, Sn, Ta, W, Os, Ir, Pt, Au, and Bi, i.e., the first additional element, relative to the entire wire. Here, when the wire of the present invention further contains Au on its surface, as described above, the "total concentration of the first additional element relative to the entire wire" in condition (A) can be understood as "the total concentration of the first additional element relative to the entire wire (wherein the concentration of Au is the concentration of the core material portion)" and applied.

[0134] Regarding condition (A), from the viewpoint of realizing an alloy-coated Cu bonding wire that improves the adhesion of the second bonding portion and brings about good initial bonding of the second bonding portion, the total concentration of the first additional element relative to the entire wire is 5 mass ppm or more, preferably 10 mass ppm or more, 15 mass ppm or more, 20 mass ppm or more, or 25 mass ppm or more, more preferably 30 mass ppm or more, 40 mass ppm or more, 50 mass ppm or more, 60 mass ppm or more, or 80 mass ppm or more, and further preferably 100 mass ppm or more, 110 mass ppm or more, 120 mass ppm or more, 130 mass ppm or more, 140 mass ppm or more, or 150 mass ppm or more. In particular, when the total concentration of the first additional element relative to the entire wire is 100 mass ppm or more, it is easy to realize a bonding wire that improves the adhesion of the second bonding portion and brings about better initial bonding of the second bonding portion, so it is preferred.

[0135] Regarding condition (A), from the perspective of achieving an alloy-coated Cu bonding wire that improves the adhesion of the second bonding portion and brings about good initial bonding properties of the second bonding portion, the total concentration of the first additional element relative to the entire wire is 450 mass ppm or less. The upper limit of the total concentration of the first additional element may also be 440 mass ppm or less, 420 mass ppm or less, 400 mass ppm or less, etc. In addition, in the case where the first additional element contains one or more elements selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, and Zn (hereinafter also referred to as "1a additional elements"), the upper limit of the total concentration of the 1a additional element may be 200 mass ppm or less, 180 mass ppm or less, 160 mass ppm or less, or 150 mass ppm or less. When the first additional element contains one or more elements selected from the group consisting of Zr, Nb, Mo, Ru, Rh, and Sn (hereinafter also referred to as "1b additional elements"), the upper limit of the total concentration of the 1b additional elements can be set to less than 350 mass ppm, less than 340 mass ppm, less than 320 mass ppm, or less than 300 mass ppm, etc.

[0136] In the wire of the present invention, from the viewpoint of realizing a bonding wire that improves the adhesion of the second bonding portion and exhibits better initial bonding properties of the second bonding portion, it is preferred that the first additional element be contained in the Cu core material.

[0137] The wire of the present invention may also contain one or more elements ("second additional elements") selected from the group consisting of B, P and Mg. In the case where the wire of the present invention contains a second additional element, the total concentration of the second additional element relative to the entire wire is preferably 1 mass ppm or more. Thus, a bonding wire with a better crimping shape of the first bonding portion can be achieved. The total concentration of the second additional element relative to the entire wire is more preferably 2 mass ppm or more, further preferably 3 mass ppm or more, 5 mass ppm or more, 8 mass ppm or more, 10 mass ppm or more, 15 mass ppm or more or 20 mass ppm or more. From the viewpoint of inhibiting the hardening of the wire and reducing chip damage during the first bonding, the total concentration of the second additional element is preferably 100 mass ppm or less, more preferably 90 mass ppm or less, 80 mass ppm or less, 70 mass ppm or less, 60 mass ppm or less or 50 mass ppm or less. Therefore, in a preferred embodiment, the wire of the present invention contains a second additional element, and the total concentration of the second additional element relative to the entire wire is 1 mass ppm or more and 100 mass ppm or less.

[0138] When the wire of the present invention contains a second additive element, the second additive element may be contained in either the Cu core material or the coating layer, or in both. From the viewpoint of realizing a bonding wire with a better crimping shape of the first bonding portion, it is preferred that the second additive element be contained in the Cu core material.

[0139] The wire of the present invention may also contain one or more elements ("third additional elements") selected from the group consisting of Se, Te, As and Sb. In the case where the wire of the present invention contains the third additional element, the total concentration of the third additional element relative to the entire wire is preferably 1 mass ppm or more. Thus, the bonding reliability of the first bonding portion under a high temperature and high humidity environment can be improved. The total concentration of the third additional element relative to the entire wire is more preferably 2 mass ppm or more, further preferably 3 mass ppm or more, 5 mass ppm or more, 8 mass ppm or more, 10 mass ppm or more, 15 mass ppm or more or 20 mass ppm or more. From the perspective of achieving a good FAB shape and a good crimping shape of the first bonding portion, the total concentration of the third additional element is preferably 100 mass ppm or less, more preferably 90 mass ppm or less, 80 mass ppm or less, 70 mass ppm or less, 60 mass ppm or less or 50 mass ppm or less. Therefore, in a preferred embodiment, the wire of the present invention contains the third additional element, and the total concentration of the third additional element relative to the entire wire is 1 mass ppm or more and 100 mass ppm or less.

[0140] When the wire of the present invention contains the third additive element, the third additive element may be contained in either the Cu core material or the coating layer, or in both. From the viewpoint of realizing a bonding wire that provides better bonding reliability of the first bonding portion under a high temperature and high humidity environment, it is preferred that the third additive element be contained in the coating layer.

[0141] The wire of the present invention may also contain one or more elements selected from the group consisting of Ga and Ge ("fourth additional element"). In the case where the wire of the present invention contains the fourth additional element, the total concentration of the fourth additional element relative to the entire wire is preferably 0.011 mass % or more. Thereby, the bonding reliability of the first bonding portion under a high temperature environment can be improved. The total concentration of the fourth additional element relative to the entire wire is more preferably 0.015 mass %, further preferably 0.02 mass %, 0.025 mass %, 0.03 mass %, 0.031 mass %, 0.035 mass %, 0.04 mass %, 0.05 mass %, 0.07 mass %, 0.09 mass %, 0.1 mass %, 0.12 mass %, 0.14 mass %, 0.15 mass % or more or 0.2 mass % or more. From the viewpoint of achieving a good FAB shape, a good crimping shape of the first joint portion, and a good initial bondability of the second joint portion, the total concentration of the fourth additional element is preferably 1.5 mass % or less, more preferably 1.4 mass % or less, 1.3 mass % or less, or 1.2 mass % or less. Therefore, in a preferred embodiment, the wire of the present invention contains the fourth additional element, and the total concentration of the fourth additional element relative to the entire wire is 0.011 mass % or more and 1.5 mass % or less.

[0142] When the wire of the present invention contains the fourth additional element, the fourth additional element may be contained in either one of the Cu core material and the coating layer, or may be contained in both.

[0143] The wire of the present invention may also contain one or more elements selected from the group consisting of In and Ag ("fifth additional element"). In the case where the wire of the present invention contains the fifth additional element, the total concentration of the fifth additional element relative to the entire wire is preferably 1 mass ppm or more. Thus, good bonding reliability of the second bonding portion can be achieved even in a more severe high temperature environment (e.g., 200°C). The total concentration of the fifth additional element relative to the entire wire is preferably 2 mass ppm or more, 3 mass ppm or more, 4 mass ppm or more, or 5 mass ppm or more, more preferably 6 mass ppm or more, 8 mass ppm or more, or 10 mass ppm or more, further preferably 20 mass ppm or more, 30 mass ppm or more, or 40 mass ppm or more, and further preferably 50 mass ppm or more, 60 mass ppm or more, or 70 mass ppm or more. Regarding the upper limit of the concentration of the fifth additional element relative to the entire wire, even if it is contained above, the effect of improving the bonding reliability of the second bonding portion under a high temperature environment reaches its peak, so considering the cost, etc., the upper limit of the concentration of the fifth additional element relative to the entire wire can be set to, for example, 500 mass ppm or less, 480 mass ppm or less, 460 mass ppm or less, 450 mass ppm or less, etc. Therefore, in a preferred embodiment, the wire of the present invention contains a fifth additional element, and the total concentration of the fifth additional element relative to the entire wire is 1 mass ppm or more and 500 mass ppm or less.

[0144] When the wire of the present invention contains the fifth additive element, the fifth additive element may be contained in either the Cu core material or the coating layer, or in both of them. From the viewpoint of realizing a bonding wire that exhibits good bonding reliability of the second bonding portion under a severe high temperature environment, it is preferred that the fifth additive element be contained in the Cu core material.

[0145] The contents of the first additional element, the second additional element, the third additional element, the fourth additional element, and the fifth additional element in the wire can be measured by the method described in “Measurement of Element Content” described later.

[0146] In the wire of the present invention, the total concentration of Cu, Ni, and Pd can be, for example, 98.5 mass % or more, 98.6 mass % or more, 98.7 mass % or more, or 98.8 mass % or more.

[0147] The diameter of the wire of the present invention is not particularly limited and can be appropriately determined according to the specific purpose, but can be preferably set to 13 μm or more, 15 μm or more, 18 μm or more, or 20 μm or more. The upper limit of the diameter is not particularly limited, and can be, for example, 80 μm or less, 70 μm or less, or 50 μm or less.

[0148] The wire of the present invention brings about a good FAB shape, and the initial bonding of the second bonding part is good, represented by the tightness of the second bonding part, and the electrochemical corrosion in a high temperature environment is suppressed to bring about good bonding reliability of the second bonding part. Therefore, the bonding wire of the present invention can be suitably used to connect the electrode on the semiconductor chip to the external terminal such as the electrode on the lead frame or the substrate.

[0149] <Method for producing thread>

[0150] An example of the method for producing the bonding wire of the present invention will be described.

[0151] Copper having a purity of 4N (99.99 mass % or more) was used as the raw copper, and an ingot containing each dopant was obtained by the method described below.

[0152] As the method of adding dopants such as the first additional element and, when adding, the second additional element, the third additional element, the fourth additional element, and the fifth additional element, for example, there are methods of including the dopant in the Cu core material, including the dopant in the coating layer, coating the surface of the Cu core material, coating the surface of the coating layer, and combinations of these methods, and these methods may be appropriately selected. In the method of including the dopant in the Cu core material, the dopant component may be directly added to Cu, or a master alloy containing a few percent of the dopant component may be used. In the method of including the dopant in the coating layer, the dopant may be included in the Pd, Ni plating bath (in the case of wet plating) or the target (in the case of dry plating) when forming the coating layer. In the method of coating the surface of the Cu core material or the method of coating the surface of the coating layer, the surface of the Cu core material or the surface of the coating layer is used as the coating surface, and the coating is carried out from (1) coating the aqueous solution. dry The coating treatment may be one or more selected from heat treatment, (2) plating method (wet method), and (3) vapor deposition method (dry method).

[0153] The ingot is forged, rolled, and drawn to produce a wire (hereinafter also referred to as an "intermediate wire") made of Cu or a Cu alloy having a diameter of about 0.7 to 2.0 mm.

[0154] As a method for forming a coating layer on the surface of the Cu core material, electroplating, electroless plating, evaporation method, etc. can be used, but electroplating that can stably control the film thickness is preferred in industry. For example, a coating layer can be formed on the surface of the intermediate wire. In addition, the coating layer can be coated at the stage of ingot casting, or, after the intermediate wire is further thinned by wire drawing (for example, after drawing to the final wire diameter), a coating layer can be formed on the surface of the Cu core material. The coating layer can be formed, for example, by providing a PdNi alloy layer containing Pd and Ni at a specified ratio on the surface of the Cu core material. From the viewpoint of forming a coating layer with excellent adhesion to the Cu core material, it can also be formed by providing a PdNi alloy layer containing Pd and Ni at a specified ratio after impact plating of a conductive metal on the surface of the Cu core material. In addition, after forming a PdNi alloy layer containing Pd and Ni at a specified ratio, more than one layer containing Pd and Ni (for example, a Pd layer, a Ni layer, a PdNi alloy layer) can be further provided.

[0155] When forming a wire containing Au on the surface, it can be formed by providing an Au layer on the surface of the coating layer in the same method as described above.

[0156] In the wire drawing process, the wire is drawn to the final wire diameter (about 13 to 80 μm in diameter) by a wire drawing device using a diamond die. In addition, as a heat treatment, in addition to the tempering heat treatment performed at the final wire diameter, an intermediate heat treatment performed in the middle of the wire drawing process can also be implemented.

[0157] [Semiconductor devices]

[0158] A semiconductor device can be manufactured by connecting electrodes on a semiconductor chip and external terminals such as electrodes on a lead frame or a circuit board using the bonding wire for a semiconductor device of the present invention.

[0159] In one embodiment, a semiconductor device of the present invention includes a circuit substrate, a semiconductor chip, and a bonding wire for electrically connecting the circuit substrate and the semiconductor chip, wherein the bonding wire is the wire of the present invention.

[0160] In the semiconductor device of the present invention, the circuit substrate and the semiconductor chip are not particularly limited, and known circuit substrates and semiconductor chips that can be used to constitute a semiconductor device can be used. Alternatively, a lead frame can be used instead of a circuit substrate. For example, as in the semiconductor device described in Japanese Patent Publication No. 2020-150116, a semiconductor device having a lead frame and a semiconductor chip mounted on the lead frame can also be provided.

[0161] Examples of semiconductor devices include various semiconductor devices used in electrical products (e.g., computers, mobile phones, digital cameras, televisions, air conditioners, solar power generation systems, etc.) and vehicles (e.g., motorcycles, automobiles, trains, ships, and airplanes, etc.).

[0162] [Example]

[0163] Hereinafter, the present invention will be described in detail with reference to examples, but the present invention is not limited to the examples described below.

[0164] (sample)

[0165] First, the method for preparing the sample is described. The raw copper used is copper with a purity of 4N (99.99 mass % or more). In addition, the first additional element, and in the case of addition, the second additional element, the third additional element, the fourth additional element, and the fifth additional element use raw materials with a purity of 3N or more, or use a master alloy containing these additional elements in Cu at a few percent.

[0166] The core material Cu alloy is first loaded into a graphite crucible and heated in a high frequency furnace under N 2 After being heated to 1090-1800°C in an inert atmosphere such as Ni gas or Ar gas and melted, an ingot with a diameter of 3-6 mm is produced by continuous casting. Next, the obtained ingot is subjected to wire drawing to produce an intermediate wire with a diameter of 0.7-2.0 mm. During the wire drawing process, a commercially available lubricating liquid is used, and the wire drawing speed is set to 20-150 m / min. The coating layer is formed by electroplating. Some wires (Examples No. 5, 9, 15, 27, 33, 36) have an Au layer on the PdNi alloy layer. The plating solution is prepared as Pd-Ni plating solution and Au plating solution, which are appropriately prepared and used.

[0167] After that, the wire is further processed by wire drawing and other processes until the final wire diameter is If necessary, an intermediate heat treatment of 300 to 700°C for 2 to 15 seconds is performed once or twice during the wire drawing process. When the intermediate heat treatment is performed, the wire is continuously purged while N 2 After the wire is processed to the final diameter, the wire is continuously purged while N 2 The tempering heat treatment is performed while the gas or Ar gas flows. The heat treatment temperature of the tempering heat treatment is set to 200-600°C, the wire conveying speed is set to 20-200m / min, and the heat treatment time is set to 0.2-1.0 seconds. When the coating layer is thin, the heat treatment temperature is set to low and the wire conveying speed is set to fast. When the coating layer is thick, the heat treatment temperature is set to high and the wire conveying speed is set to slow.

[0168] (Test and evaluation methods)

[0169] Hereinafter, the test and evaluation methods will be described.

[0170] [Line surface composition analysis using Auger electron spectroscopy (AES)]

[0171] Regarding a wire containing Au on the surface of the wire, the concentration of Au on the surface of the wire is determined by measuring the surface of the wire using Auger electron spectroscopy (AES) as follows, with the surface of the wire as a measurement surface.

[0172] First, the bonding wire to be measured is fixed to the sample holder in a straight line. Next, the wire is positioned so that the center of the width of the wire in the direction perpendicular to the wire axis becomes the center of the width of the measurement surface, and the measurement surface is determined so that the width of the measurement surface is 5% to 15% of the wire diameter. The length of the measurement surface is 5 times the width of the measurement surface. Then, an AES device (PHI-700 manufactured by ULVAC﹒PHI) is used to perform a composition analysis of the wire surface at an acceleration voltage of 10 kV to determine the surface Au concentration (atomic %).

[0173] In addition, the composition analysis by AES was performed on three measurement surfaces separated by more than 1 mm in the linear axis direction, and the arithmetic mean value was used. When calculating the Au concentration on the surface, gas components such as carbon (C), sulfur (S), oxygen (O), and nitrogen (N), and non-metallic elements were not considered.

[0174] [Thickness analysis of coating layer using Auger electron spectroscopy (AES)]

[0175] The thickness of the coating layer was analyzed using depth analysis using AES. Depth analysis using AES analyzes the composition changes in the depth direction by alternately performing composition analysis and sputtering, and can obtain the concentration changes of each element from the line surface to the depth (center) direction (the so-called concentration distribution in the depth direction).

[0176] Specifically, after 1) performing composition analysis on the line surface using AES, 2) sputtering using Ar and 3) composition analysis on the surface after sputtering are repeated to obtain the concentration distribution in the depth direction. + ions, and the acceleration voltage was 2 kV. In addition, in the composition analysis of the surface in 1) and 3), the conditions for calculating the size of the measurement surface or the composition analysis by AES and the concentration of each element are set to be the same as those described in the above [Linear surface composition analysis by Auger electron spectroscopy (AES)]. When obtaining the concentration distribution in the depth direction by AES, the measurement is performed in such a way that the measurement points in the depth direction become 50 or more points in the coating layer.

[0177] The acquisition of the concentration distribution in the depth direction was performed on three measurement surfaces that were separated from each other by 1 mm or more in the linear axis direction.

[0178] - The thickness of the coating layer and the total number of measurement points of the coating layer -

[0179] In the obtained concentration distribution in the depth direction, the concentration distribution is checked from the line surface to the line center side, and the concentration C of Pd is Pd (atomic %) and Ni concentration C Ni The depth position Z1 to C where the total of (atomic %) first reaches 90 atomic % or more Pd and C Ni The distance to the depth position Z2 (where Z2>Z1) where the total of the first decreases to less than 90 atomic % is calculated as the measured thickness of the coating layer. Furthermore, the total number of measurement points from the depth position Z1 to the depth position Z2 is calculated as the total number of measurement points of the coating layer. The thickness of the coating layer is the arithmetic mean of the values ​​obtained for the three measurement surfaces. In addition, for the lines of the embodiment, it was confirmed that the total number of measurement points of the coating layer was 50 to 100 points.

[0180] The depth measured by AES analysis is obtained as the product of the sputtering rate and the time. 2 The depth of SiO was determined by AES. 2 The unit of the coating thickness is SiO 2 Conversion value.

[0181] - The total number of measurement points whose average value X and absolute deviation from the average value X are within the specified range -

[0182] In the obtained concentration distribution in the depth direction, the Pd concentration C of all the measurement points in the coating layer is Pd (atomic %) and Ni concentration C Ni (atomic %) ratio C Pd / C Ni The arithmetic mean is calculated to obtain the average value X. Next, the ratio C of all the measurement points of the coating layer is calculated. Pd / C Ni , calculate the absolute deviation from the average value X, and find the total number of measurement points whose absolute deviation from the average value X is within 0.3X and the total number of measurement points whose absolute deviation from the average value X is within 0.2X. The average value X is the arithmetic mean of the values ​​obtained for the three measurement surfaces.

[0183] -C Pd or C Ni The slope of the approximate straight line (the difference between the maximum and minimum values ​​in the depth range of the coating layer) -

[0184] For all the measurement points of the coating layer, the least square method was used to calculate the C Pd (atomic %) or C Ni (atomic %) is approximated by a straight line, and the difference (atomic %) between the maximum and minimum values ​​of the approximate straight line in the depth range of the coating layer is calculated. Here, when the average value X is less than 1, the least square method is used for all the measurement points of the coating layer. Ni (atomic %) was linearly approximated, and when the average value X was greater than 1, the least square method was used for all the measurement points of the coating layer. Pd The difference (atomic %) between the maximum value and the minimum value of the approximate straight line in the depth range of the coating layer was calculated by taking the arithmetic mean of the values ​​obtained for the three measurement surfaces.

[0185] [Determination of element content]

[0186] The contents of the first additive element, the second additive element, the third additive element, the fourth additive element, and the fifth additive element in the wire are detected as the concentration of the elements contained in the entire wire by analyzing the liquid obtained by dissolving the bonding wire with a strong acid using an ICP emission spectrometer or an ICP mass spectrometer. As the analysis device, ICP-OES ("PS3520UVDDII" manufactured by Hitachi High-Tech Science) or ICP-MS ("Agilent7700x ICP-MS" manufactured by Agilent Technologies) is used. In addition, for the wire containing Au on its surface, the concentration of Au as the first additive element is determined by exposing the cross section of the wire and measuring its Cu core material portion using an electron beam microanalyzer (EPMA) or a secondary ion mass spectrometer (SIMS).

[0187] [FAB shape]

[0188] The FAB shape was evaluated by making FAB on the lead frame using a commercially available wire bonding machine and observing it with a scanning electron microscope (SEM) (evaluation number N = 100). In addition, the FAB was set to a current value of 30 to 75 mA, a gap of EFO of 762 μm, and a tail length of 254 μm, while N was charged at a flow rate of 0.4 to 0.6 L / min. 2 +5%H 2 The diameter of the wire formed by gas flow is 1.5 to 1.9 times the wire diameter. The FAB shape is judged as good if it is a true spherical shape, and poor if it is eccentric, deformed, or poorly melted. Then, it is evaluated according to the following criteria.

[0189] Evaluation criteria:

[0190] ◎: Less than 5 defects

[0191] ○: 6 to 10 defects (no problem in practical use)

[0192] ×: More than 11 defects

[0193] [Initial Bonding Property of Second Bonding Section]

[0194] The initial bonding property of the second joint portion is evaluated by measuring and observing the bonding strength and adhesion of the second joint portion. Specifically, the bonding strength of the second joint portion is measured by a tensile test. In addition, the adhesion of the second joint portion is evaluated by SEM observation of the cross section of the second joint portion.

[0195] - Bonding strength of the second bonding portion -

[0196] Using a commercially available wire bonding machine, 80 wires in each of the vertical and horizontal directions (320 wires in total) were bonded to a Cu alloy lead frame that had been plated with Ag, thereby producing an evaluation sample.

[0197] Then, a tensile test was performed on the second bonded portion. The value of the tensile strength was the arithmetic mean of the measured values ​​of 60 pieces in total, 15 pieces in each direction.

[0198] - Adhesion of the second joint -

[0199] Using a commercially available wire bonding machine, 40 wires in each of the vertical and horizontal directions (160 wires in total) were bonded to a Cu alloy lead frame that had been subjected to PPF plating, thereby producing an evaluation sample.

[0200] Then, the second joint portion was cross-sectioned and ground using an ion beam to prepare a sample for SEM observation. Specifically, when the evaluation sample is observed from directly above in a direction perpendicular to the main surface of the lead frame, the second joint portion was cut and cross-sectioned at a position where the width of the second joint portion was the largest, and the sample for SEM observation was prepared. Here, the width of the second joint portion refers to Figure 1 The left-right dimension of the second joint portion 10 is determined by ion beam cross-sectional milling at a position where the width of the second joint portion is substantially the largest. Figure 1 The width of the line is perpendicular to the center X of the line (along Figure 1 AA double dotted line).

[0201] For the obtained sample for SEM observation, the cross section of the second bonding portion was observed by SEM, and the width ( Figure 2 L2) relative to the full width of the second joint ( Figure 2The ratio of L2 to L1, that is, the close contact ratio (%) (= L2 / L1×100) was calculated. The three second joining portions were observed and calculated, and the arithmetic mean value was used.

[0202] Evaluation was performed based on the following criteria based on the bonding strength (tensile strength) and adhesion (adhesion ratio) of the obtained second bonding portion.

[0203] Evaluation criteria:

[0204] ◎◎: Adhesion rate 90% or more and tensile strength 8gf or more

[0205] ◎: Adhesion rate 90% or more and tensile strength 6gf or less, less than 8gf, or tensile strength 12gf or more and adhesion rate 80% or more, less than 90%

[0206] ○: Adhesion rate 80% or more and less than 90% and tensile strength 6gf or more and less than 12gf

[0207] ×: Adhesion rate is less than 80% or tensile strength is less than 6gf

[0208] [Joining Reliability of Second Joining Section]

[0209] The bonding reliability of the second bonding portion was evaluated by a high temperature storage life test (HTSL: High Temperature Storage Life Test).

[0210] The sample formed by wedge bonding the lead part of the lead frame using a commercially available wire bonding machine was sealed with a commercially available thermosetting epoxy resin to prepare a sample for the bonding reliability test of the second bonding part. The lead frame used was a Cu alloy lead frame with 1 to 3 μm Ag plating. The prepared sample for bonding reliability evaluation was exposed to an environment with a temperature of 175°C using a high-temperature constant temperature machine. The bonding life of the second bonding part is the time when the tensile test of the wedge bonding part is carried out every 500 hours and the value of the tensile strength becomes 1 / 2 of the tensile strength obtained initially. The value of the tensile strength uses the arithmetic mean of the measured values ​​at 50 randomly selected wedge bonding parts. The tensile test after the high-temperature placement test is carried out after the resin is removed by acid treatment to expose the wedge bonding part. Then, evaluation is performed according to the following criteria.

[0211] Evaluation criteria:

[0212] ◎◎: Joint life more than 3000 hours

[0213] ◎: Bonding life is more than 2000 hours and less than 3000 hours

[0214] ○: Bonding life is 1000 hours or more and less than 2000 hours

[0215] ×: Bonding life is less than 1000 hours

[0216] [Joint Reliability of First Joining Section]

[0217] The bonding reliability of the first bonding portion is tested by both a high temperature storage life test (HTSL: High Temperature Storage Life Test) and a high temperature and humidity test (HAST: Highly Accelerated Temperature and Humidity Stress Test).

[0218] -HTSL-

[0219] A sample was formed by ball bonding an electrode formed by forming an alloy film of Al-1.0 mass% Si-0.5 mass% Cu with a thickness of 1.5 μm on a silicon substrate on a general metal frame using a commercially available wire bonding machine, and then sealed with a commercially available thermosetting epoxy resin to prepare a sample for the bonding reliability test of the first bonding portion. The ball was formed under the conditions described in the above [FAB shape] column. The prepared sample for bonding reliability evaluation was exposed to an environment with a temperature of 175°C using a high-temperature thermostat. The bonding life of the first bonding portion is the time when a shear test of the ball bonding portion is performed every 500 hours, and the shear strength value becomes 1 / 2 of the initial shear strength. The shear strength value uses the arithmetic mean of the measured values ​​at 50 randomly selected ball bonding portions. The shear test after the high-temperature placement test is performed after the resin is removed by acid treatment to expose the ball bonding portion. Then, the evaluation is performed according to the following criteria.

[0220] Evaluation criteria:

[0221] ◎: Bonding life more than 2000 hours

[0222] ○: Bonding life is 1000 hours or more and less than 2000 hours

[0223] ×: Bonding life is less than 1000 hours

[0224] -HAST-

[0225] The sample for evaluating the reliability of the first joint made in the same steps as above was exposed to a high temperature and high humidity environment of 130°C and 85% relative humidity using an unsaturated pressure cooker tester, and a bias of 7V was applied. The joint life of the first joint is the time when the shear test of the ball joint is carried out every 48 hours, and the shear strength value becomes 1 / 2 of the initial shear strength. The shear strength value uses the arithmetic mean of the measured values ​​of 50 randomly selected ball joints. The shear test is carried out after the ball joint is exposed by removing the resin through acid treatment. Then, the evaluation is carried out according to the following criteria.

[0226] Evaluation criteria:

[0227] ◎: Joint life more than 384 hours

[0228] ○: Bonding life 240 hours or more and less than 384 hours

[0229] ×: Bonding life is less than 240 hours

[0230] [Crimp shape]

[0231] The evaluation of the crimping shape of the first joint (the flattened shape of the ball) is performed as follows: a ball is formed under the conditions described in the [FAB shape] column using a commercially available wire bonding machine, and the ball is crimped and bonded to an electrode formed on a Si substrate with a thickness of 1.5 μm and an Al-1.0 mass% Si-0.5 mass% Cu alloy film, and observed from directly above using an optical microscope (evaluation number N = 100). In the determination of the flattened shape of the ball, it is judged to be good if the flattened shape is close to a perfect circle, and it is judged to be poor if it is an elliptical or petal-shaped shape. Then, the evaluation is performed according to the following criteria.

[0232] Evaluation criteria:

[0233] ◎: No defect

[0234] ○: 1 to 5 defects (no problem in practical use)

[0235] ×: More than 6 defects

[0236] Tables 1 and 2 show the evaluation results of Examples and Comparative Examples.

[0237] [Table 1]

[0238]

[0239] [Table 2]

[0240]

[0241] Description of Reference Numerals

[0242] 1Joint line (wire)

[0243] 2 Measurement surface

[0244] 10 Second joint

[0245] 50 external terminals

[0246] The center of the X-ray width

[0247] Width of W wire (wire diameter)

[0248] wa Width of measuring surface

[0249] l a Measuring surface length

[0250] L1 Full width of the second joint

[0251] L2 The width of the second joint center line and the external terminal

Claims

1. A bonding wire comprising a core material made of Cu or a Cu alloy and a coating layer formed on the surface of the core material and having a total concentration of Pd and Ni of 90 atomic % or more, In the concentration distribution in the depth direction of the line obtained by measuring by Auger electron spectroscopy so that the number of measurement points in the depth direction is 50 or more in the coating layer, The thickness of the coating layer is not less than 10 nm and not more than 130 nm. When the Pd concentration C of all measurement points in the coating layer is Pd (atomic %) and Ni concentration C Ni (atomic %) ratio C Pd / C Ni When the average value of is set to X, the average value X is greater than or equal to 0.1 and less than or equal to 35.0, In the coating layer, the total number of measurement points whose absolute deviation from the average value X is within 0.3X is 50% or more relative to the total number of measurement points in the coating layer, The bonding wire satisfies the following condition (A), (A) Contains one or more elements selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Zn, Zr, Nb, Mo, Ru, Rh, Sn, Ta, W, Os, Ir, Pt, Au, and Bi as a first additional element, and the total concentration of the first additional element relative to the entire wire is not less than 5 mass ppm and not more than 450 mass ppm.

2. A bonding wire comprising a core material made of Cu or a Cu alloy and a coating layer formed on the surface of the core material and having a total concentration of Pd and Ni of 90 atomic % or more, In the concentration distribution in the depth direction of the line obtained by measuring by Auger electron spectroscopy so that the number of measurement points in the depth direction is 50 or more in the coating layer, The thickness of the coating layer is not less than 10 nm and not more than 130 nm. When the Pd concentration C of all measurement points in the coating layer is Pd (atomic %) and Ni concentration C Ni (atomic %) ratio C Pd / C Ni When the average value of is set to X, the average value X is greater than or equal to 0.1 and less than or equal to 35.0, In the coating layer, the total number of measurement points whose absolute deviation from the average value X is within 0.3X is 50% or more relative to the total number of measurement points in the coating layer, The bonding wire satisfies the following conditions (A) and (B), (A) containing one or more elements selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Zn, Zr, Nb, Mo, Ru, Rh, Sn, Ta, W, Os, Ir, Pt, Au, and Bi as a first additional element, wherein the total concentration of the first additional element relative to the entire wire is 5 mass ppm or more and 450 mass ppm or less, wherein the concentration of Au is the concentration of the core material portion, (B) Au is contained on the surface of the wire, and the concentration of Au is 0.5 mass % or less based on the entire wire.

3. The bonding wire according to claim 1 or 2, In the coating layer, the total number of measurement points whose absolute deviation from the average value X is within 0.2X is 50% or more relative to the total number of measurement points in the coating layer.

4. The bonding wire according to any one of claims 1 to 3, For all the measurement points of the coating layer, the least square method was used to calculate the C Pd or C Ni When a straight line approximation is performed, the difference between the maximum value and the minimum value of the approximate straight line within the depth range of the coating layer is 20 atomic % or less.

5. The bonding wire according to any one of claims 1 to 4, The concentration distribution in the depth direction of the wire was obtained by digging from the surface of the wire downward in the depth direction by Ar sputtering and measuring by AES under the following conditions: Conditions: Positioning is performed so that the center of the wire width is the center of the measurement surface width, the measurement surface width is 5% to 15% of the wire diameter, and the measurement surface length is 5 times the measurement surface width.

6. The bonding wire according to any one of claims 1 to 5, One or more elements selected from the group consisting of B, P, and Mg are contained as second additional elements, and the total concentration of the second additional elements relative to the entire wire is 1 mass ppm or more and 100 mass ppm or less.

7. The bonding wire according to any one of claims 1 to 6, One or more elements selected from the group consisting of Se, Te, As, and Sb are contained as third additional elements, and the total concentration of the third additional elements relative to the entire wire is 1 mass ppm or more and 100 mass ppm or less.

8. The bonding wire according to any one of claims 1 to 7, One or more elements selected from the group consisting of Ga and Ge are contained as fourth additional elements, and the total concentration of the fourth additional elements relative to the entire wire is 0.011 mass % or more and 1.5 mass % or less.

9. The bonding wire according to any one of claims 1 to 8, One or more elements selected from the group consisting of In and Ag are contained as fifth additional elements, and the total concentration of the fifth additional elements with respect to the entire wire is 1 mass ppm or more and 500 mass ppm or less.

Citation Information

Patent Citations

  • Copper alloy wire for connecting semiconductor element

    JP1986048543A

  • Bonding wire and integrated circuit device using the same

    JP2005167020A

  • Corrosion and Moisture Resistant Copper Based Bonding Wire Containing Nickel

    JP2018503743A

  • Semiconductor device and manufacturing method thereof

    JP2020150116A

  • Bonding wire for semiconductor device

    WO2017013796A1

Cited By

  • Method for analyzing target coverage rate by corrosion method

    CN120870208A